Estudos genéticos em raias do gênero Potamotrygon (Chondrichthyes: Myliobatiformes: Potamotrygonidae) na Bacia do Rio Paraná - Cruz, Vanessa Paes da [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The stingrays Potamotrygonidae family are important components of Neotropical ichthyofauna, being completely restricted to the main river systems of South America four genera are related in that family: Heliotrygon, Paratrygon, and Plesiotrygon Potamotrygon. In Paraná River Basin, the species most frequently are Potamotrygon motoro and Potamotrygon falkneri. Both species occur only in the region of the middle Paraná, downstream of a major natural geographic barrier, the Waterfalls of Seven Falls. However, after the construction of the Itaipu Hydroelectric, many aquatic species colonized the high Paraná, including stingrays, which came to play the role of invasive species. Currently, the lanes are set up in the region Ilha Solteira - SP (high Paraná). Aiming to analyze the process of invasion and colonization of species Potamotrygon motoro and P. falkneri in the Paraná River Basin were carried out molecular genetic studies using mitochondrial and nuclear genes. The gene Cytochrome Oxidase subunit I (COI) was first developed for molecular identification of species. Gene sequences were subsequently ATPase 6/8, Cyt-B and D-loop control region were obtained for population analyzes. The genetic diversity found for the COI gene between species was 2.0%, considered low when compared to results obtained in other species of fish. In population analyzes in P. motoro, diversity intraspecific was very low for all genes with multiple individuals sharing the same haplotype. In P. falkneri values were similar to that detected in P. motoro, although the values of genetic differentiation elevated but not statistically significant. Diantes results mean that the low genetic differentiation detected for both species under study, may be related to the short time of colonization (under 30) or the fact that the marker is not sensitive enough to detect such genetic differences. With this, it was necessary to search for other markers to check more efficiently...

As raias da família Potamotrygonidae são importantes componentes da ictiofauna Neotropical, sendo completamente restritas aos principais sistemas fluviais da América do Sul. Quatro gêneros são relacionados nessa familia: Heliotrygon, Paratrygon, Plesiotrygon e Potamotrygon. Na Bacia do Rio Paraná, as espécies de maior frequência são Potamotrygon motoro e Potamotrygon falkneri. Ambas as espécies ocorriam somente na região do médio Paraná, a jusante de uma importante barreira geográfica natural, as Cachoeiras de Sete-Quedas. Porém, após a construção da Usina Hidrelétrica de Itaipu, muitas espécies antes existentes apenas na parte baixa da bacia hidrográfica, iniciaram um processo de dispersão e colonizaram o Alto Paraná, incluindo as raias, as quais passaram a desempenhar o papel de espécies invasoras. Atualmente, as raias estão estabelecidas até a região de Ilha Solteira-SP (alto Paraná), com possibilidade de já terem atingido pontos mais superiores nesta bacia. Com o objetivo de analisar o processo de invasão e colonização das espécies Potamotrygon motoro e P. falkneri na bacia do Rio Paraná, foram realizados estudos genéticos moleculares utilizando genes mitocondriais e nucleares. O gene Citocromo Oxidase C subunidade I (COI) foi utilizado primeiramente para a identificação molecular das espécies, posteriormente, sequências dos genes ATPase 6/8, Cyt-B e região controle D-loop foram obtidas para análises populacionais. A divergência genética encontrada para o gene COI entre as espécies foi de 2,0%, considerada baixa quando comparada com resultados obtidos em outras espécies de peixes. Nas análises populacionais em P. motoro, a diversidade intra-específica foi baixa para todos os genes, com vários indivíduos compartilhando os mesmos haplótipos. Em P. falkneri, os valores foram semelhantes aos detectados em P. motoro, porém com valores de diferenciação genética elevados mas não significativos...
Keywords: Genetica de populações; Raia (Peixe); Parana, Rio, Bacia; |a Populations genetics